PENYULUHAN KESEHATAN REPRODUKSI DALAM UPAYA PEMBANGUNAN REMAJA SEHAT DI DESA SUKAMUKTI KABUPATEN GARUT - Setiati, Atu; Rahadianti, Ayu (Muria Jurnal Layanan Masyarakat, 2023)
Sukamukti Village is a village that was chosen to get the â€œPower To Youthâ€Program by Garut Regency because it has problems with groups of teenagers who marry early and get many legal dispensations. This is a major problem because the impact will be detrimental to teenagers as the next generation. In an effort to develop reproductive health, there must be a program of activities to make changes. The purpose of reproductive health counseling is to increase literacy, insight, knowledge so as to increase adolescent awareness of the importance of maintaining reproductive health. The results of this service make the Banyuresi Youth Communication Forum in Sukamukti Village more appreciated by the government and the community, get legal legality by the village government as a CSO that focuses on teenagers, add insight and knowledge about reproductive health, and can be productive with youth posyandu.